The p53 tumor suppressor regulates AKR1B1 expression, a metastasis-promoting gene in breast cancer - Di Benedetto, Carolina; Borini Etichetti, Carla; Cocordano, Nabila; Cantoia, Alejo; Arel Zalazar, Evelyn; Bicciato, Silvio; Menacho-Márquez, Mauricio; Rosano, Germán Leandro; Girardini, Javier (Frontiers in Molecular Biosciences, 2023)
Alteration of metabolism in cancer cells is a central aspect of the mechanisms that sustain aggressive traits. Aldo–keto reductase 1 B1 (AKR1B1) catalyzes the reduction of several aldehydes to alcohols consuming NADPH. Nevertheless, the ability of AKR1B1 to reduce different substrates renders difficult to comprehensively ascertain its biological role. Recent evidence has implicated AKR1B1 in cancer; however, the mechanisms underlying its pro-oncogenic function remain largely unknown. In this work, we report that AKR1B1 expression is controlled by the p53 tumor suppressor. We found that breast cancer patients bearing wild-type TP53 have reduced AKR1B1 expression. In cancer cell lines, p53 reduced AKR1B1 mRNA and protein levels and repressed promoter activity in luciferase assays. Furthermore, chromatin immunoprecipitation assays indicated that p53 is recruited to the AKR1B1 promoter. We also observed that AKR1B1 overexpression promoted metastasis in the 4T1 orthotopic model of triple-negative breast cancer. Proteomic analysis of 4T1 cells overexpressing AKR1B1 showed that AKR1B1 exerts a marked effect on proteins related to metabolism, with a particular impact on mitochondrial function. This work provides novel insights on the link between the p53 pathway and metabolism in cancer cells and contributes to characterizing the alterations associated to the pathologic role of AKR1B1.